2022
DOI: 10.1055/s-0042-1751303
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review on Fanconi Anemia: Genetic and Diagnostic Considerations

Abstract: Fanconi anemia (FA) is an autosomal recessive disorder, both genetically and phenotypically. It is characterized by chromosomal instability, progressive bone marrow failure, susceptibility to cancer, and various other congenital abnormalities. It involves all the three cell lines of blood. So far, biallelic mutations in 21 genes and one x-linked gene have been detected and found to be associated with FA phenotype. Signs and symptoms start setting in by the age of 4 to 7 years, mainly hematological symptoms. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The matrix metalloproteinase Mmp9 is also involved in both vascular and bone development, as demonstrated in mmp9 null mice that develop bone abnormalities . MMP-9 is associated with osteoclast migration through the collagen matrix and impacts early calvarian bone development. An additional gene associated with skeletal development is fancc, which is involved in a chromosomal instability disorder named Fanconi anemia and is associated with developmental abnormalities including skeletal malformation. Several brain or neuronal genes were among the identified biomarkers. These included Ppp1r9alb, predicted to be involved in development and function of the cerebellar neural circuits and nervous system development in zebrafish and Dbh, which is expressed in the endocrine and nervous systems of zebrafish embryos, and is essential for mouse embryonic development .…”
Section: Discussionmentioning
confidence: 99%
“…The matrix metalloproteinase Mmp9 is also involved in both vascular and bone development, as demonstrated in mmp9 null mice that develop bone abnormalities . MMP-9 is associated with osteoclast migration through the collagen matrix and impacts early calvarian bone development. An additional gene associated with skeletal development is fancc, which is involved in a chromosomal instability disorder named Fanconi anemia and is associated with developmental abnormalities including skeletal malformation. Several brain or neuronal genes were among the identified biomarkers. These included Ppp1r9alb, predicted to be involved in development and function of the cerebellar neural circuits and nervous system development in zebrafish and Dbh, which is expressed in the endocrine and nervous systems of zebrafish embryos, and is essential for mouse embryonic development .…”
Section: Discussionmentioning
confidence: 99%
“…[75] Pure red cell aplasia, or Diamond-Blackfan anemia, frequently manifests as abnormalities of the bone marrow. [76] In 88-100% of cases, Schwachman-diamond syndrome is primarily characterized by neutropenia. [77] Vaccination against the human papillomavirus (eur-lex.europa.eu) lowers the chance of gynecologic cancer in women and perhaps lowers the chance of oral cancer in everyone.…”
Section: Treatment With Co-relate To Diagnosementioning
confidence: 99%
“…FANCL is a key gene involved in the FA DNA repair pathway, and its homozygous or compound heterozygous mutation can lead to the onset of Fanconi anemia (FA), which is one of the most common inherited BMFs. [3,4] FANCL is just one of the FA complementation (FANC) genes, which include a total of 22 genes, namely FANCA, FANCB, FANCC, FANCD1, FANCD2, FANCE, FANCF, FANCG, FANCI, FANCJ, FANCL, FANCM, FANCN, FANCO, FANCP, FANCQ, FANCR, FANCS, FANCT, FANCU, FANCV, and FANCW. [5][6][7] Researches have reported that heterozygous mutations in the FANC genes may lead to an increased susceptibility to tumors and acquired BMF.…”
Section: Introductionmentioning
confidence: 99%